Analisis pekerja anak pada pasar tradisional (studi kasus : pasar angso duo dan pasar baru Kota Jambi) - Andika Beremana; Zamzami Zamzami; Adi Bhakti (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2020)
This study aims to: 1) To analyze the social and economic characteristics of child labor in the traditional markets of Pasar Angso Duo and Pasar Baru Kota Jambi. 2) To analyze how much the contribution of child labor income to family income. And 3) To analyze what factors influence children working in the traditional markets of Pasar Angso Duo and Pasar Baru Kota Jambi. Based on social and economic characteristics, it can be said that the average age of child labor ranges from 7-10 years, the number of child workers who have not completed school is very large, 19 people or 76 percent. There are very large numbers of family heads of children who have not completed high school, namely 18 people or 72 percent. Furthermore, the average working hours of child laborers in the Angso Duo and Pasar Baru markets range from 7.5 to 8.5 hours.